Asteroid Dynamics as a tool for teaching Physics and Astronomy (2022)
This article presents the results of the construction and implementation of a sequence of teaching learning methodology taking on mind the Kepler’s laws, their relationship with Newton’s laws and their respective application in the classical description of the movement of asteroids in the Solar System. Is also linked the citizen science project for the asteroid identification of the international collaboration - IASC, with the intention to provide a context on the importance of the identification of asteroids in the Solar System. The implementation have been done with High School students from the club of astronomy of a district educational institution in the city of Bogotá. It is evident that the proposed activities contributed to a better understanding of the topics addressed in the classroom, and some of the difficulties that persist in the group are identified and that are tools to redesign the proposed lerning sequence.